Culture as a property of living systems - Strzałko, Jan (Anthropological Review, 1978)
Discrepancy between the sciences and the humanities is usually seen in diversity of methodologies applied by these two domains of our knowledge. The present author has presented three viewpoints concerning the question of said discrepancy. The first one is concordant with what was said above, the second one allows for formal concordance of descriptions in both the sciences and the humanities that stems from the adaptational structure of explanatory strategies. The third viewpoint, adopted here by the author, claims the real, meritorious identity of all the phenomena occurring with respect to living systems, no matter whether the man is or is not present in them. The very essence of any living system is its informational content. It is worthwhile to separate that aspect of information which is called transmission. Further considerations are focused on the population as the least self-defined systemic living unit. Interindividual transmission of information is, in general, facilitated by two carriers: genetic one and non-genetic one. The first one ensures the repetition of the structure of individuals together with all their organic and behavioral properties, including the ability for non-genetic transmission of information. The second mode of transmission serves directly for building up and maintenance of the system's structure. This latter way differs from the first one in that it may be performed at any moment of the individual's existence, not solely during processes of reproduction. Moreover, carriers of information in the second type of transmission may be highly variable, e.g., corpuscles, waves, mechanical influences, structure of heterogeneous objects, etc. Informational content of a population must meet the criterion of adaptation, that is, the persistence of a population in given environmental conditions. Since environmental conditions are constantly changing, the information must be sufficiently variable. New informational variants result from errors of transmission. Obviously, the more abundant informational content of a population, the higher its homeostatic capacity. High informational complexity of individuals is enabled by interiorization, a process of permanent, during the system's history, complication of individual structures and behavior. Complexity of populational structures, i.e., various configurations of individuals among themselves and between them and environmental factors, is facilitated by the process of exteriorization. This process is characterized by reliance upon non-genetic transmission of information. The exceptional position of man in the realm of living things is primarily due to the abundance of complex processes of exteriorizational type; a minor role is played here by interiorization, which is confined to better-developed structures and functional properties of the central nervous system. The characteristic set of exteriorizational phenomena for humans is frequently called the technologic-organizational system, or more traditionally, the culture. The author attempts to prove that the discrepancy between human and non-human systems of exteriorization does not exist qualitatively; what it actually is, is a continuous quantitative difference between systems differing in the degree of exteriorization employed in their adaptation. Toward this end, in the paper, a set of examples pertaining to the process of hominization is presented together with some instances relating to the recently living apes.